How do consumer-focused multinational enterprises affect emerging markets? - Terutomo Ozawa (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
Consumption-focused MNEs that have originated mostly since the end of World War II spread consumerism globally, prompting the Smithian goal of economic growth. Now that late industrializers have swiftly been catching up to join the ranks of advanced economies, these MNEs are eagerly setting up shop in emerging markets. This Perspective explores the general entry patterns of such MNEs and their potential impact on emerging markets.
Keywords: 330